Acessibilidade para pessoas com deficiência visual em cursos no Moodle: guia para professores - Lemos, Edith dos Santos (2015)
This dissertation was developed by the Graduate Program in Educational Technology Network, in line Educational Technology Management Research Network and its final product one set of Visually Impaired to Accessibility Guidelines in Moodle, as well as a Learning object to disclosure of the same. It is considered that education must be democratic must meet all kinds of students, including the visually impaired. To support the process of inclusion, considering the use of Virtual Environments for Teaching and Learning (AVEA), different accessibility guidelines have been designed to be observed in the creation of virtual educational resources. However, what is observed is a shortage in relation to a closer relationship between the policies and their applicability in such an environment. Considering the AVEA Moodle, this dissertation aimed to create an accessibility guidelines guide to support teachers in developing their disciplines or courses when they require assistance to make available materials for students with disabilities and present them in an Object Learning. This was developed as a resource of type Book Moodle, in order to approach the teacher's guidelines when creating a course. After development, the guidelines and the book were evaluated by teachers who used the book to create courses in Moodle, assessing the guidelines itself, as well as the usability of the feature. Also participated in the evaluation visually impaired students, and they held a course developed by the author of this research in order to assess whether the guidelines allow the creation of a more accessible way. In conclusion, after the evaluations, this research may contribute to teachers who have students with visual impairments because the way the guidelines were presented can facilitate the organization and preparation of content and visually impaired students can learn and participate equally.